(untitled) - Agnes, Michael (New Jersey, 2002)
The dictionary segment of this volume includes more than 58,000 entries providing clear, precise, and reliable definitions of all of today's most commonly used words. Widely used scientific, technical, professional, and business terms are included, as well as common abbreviations and guides to spelling, punctuation, and capitalization. Word derivations are provided to help you better understand the language and its use. All the dictionary entries in this volume appear in the top portion of each page. In the bottom portion are the corresponding thesaurus entries. These list a wide array of synonyms that can add variety to every type of writing. Students, writers, speakers, editors, crossword puzzle buffs — anyone who has a need for just the right word — will find these entries uniquely helpful and easy to use. Also from Webster's New World
Keywords: English language,English language; Dictionaries,Synonyms and antonyms